A pH Self‐Monitoring Heterogeneous Multicompartmental Proteinosome with Spatiotemporal Regulation of Insulin Transportation. Issue 12 (2nd November 2021) - Wen, Ping; Wang, Xueyi; Chen, Haixu; Appelhans, Dietmar; Liu, Xiaoman; Wang, Lei; Huang, Xin
Main observation and conclusion: Inspired by the intricate eukaryotic cell structure, the spontaneously assembling multicompartments capable of spatiotemporally regulated biomacromolecules transportation is still a challenge. Here, a heterogeneous proteinosome‐based multicompartment was designed and constructed by combining aqueous two‐phase system and Pickering emulsion methods. By loading PEGylated insulin with boronic acid group into the multicompartment and glucose oxidase (GOx) into the innermost microgel domain, a short‐ or long‐term transportation pathway of the loaded insulin was constructed by responding to the concentration of glucose. Moreover, the diminution of dynamic boronic ester bonding, the hindrance of polyethylene oxide micro‐chamber, electrostatic interaction and the swelling behavior of hydrogel triggered by GOx/glucose reaction resulted in spatiotemporally controlled multi‐pathway transportation mode with the releasing of insulin loaded inside the innermost microgel at high concentration of glucose (10 mg·mL –1 ). Specially, by incorporating rhodamine B and fluorescein labelled BSA into the multicompartment, the release procedure of the loaded insulin can be monitored by the fluorescence color‐change. Overall, a multimode microcompartment is constructed which is then expected to provide a promising platform for further therapeutic protein, gene and drug delivery, as well as towards the design of complicated cell biomimetics. Abstract : To investigate the programmed biomacromolecules transportation behaviors under both spatial and temporal control, a multicompartment with heterogeneous sub‐compartments was constructed. Due to the advantage combination of dynamic boronic ester bonding, hindrance of PEO micro‐chamber, electrostatic interaction and swelling behavior of hydrogel triggered by GOx/glucose reaction, a glucose concentration dependent and long‐term release of the insulin with spatiotemporal regulation was realized.